Isolation of a Factor from Apple that Agglutinates Erwinia amylovora - Romeiro, R. (1981)
Extracts prepared from apple seeds contain a factor (AF) capable of agglutinating cells of Erwinia amylovora. In drop agglutination tests, AF is more active in agglutinating an avirulent, acapsular strain of E. amylovora than a virulent, capsular strain. AF precipitates in agar plates with a receptor derived from boiled cells of avirulent acapsular strain and, therefore, can be located during fractionation by rocket electrophoresis. AF was heat-stable and had a pH optimum for agglutination near ≅3.6 pH. The agglutination activity was not affected by the presence of Mg(2+), Ca(2+), or EDTA. AF was separated into two fractions (AF I and AF II) by elution from a Bio-Gel P-100 column. The precipitin and agglutination activities associated with AF II were found to be present in a positively charged molecule which was sensitive to treatment with protease and trypsin and, hence, presumably resides in a protein. The approximate molecular weight of AF II was determined to be 12,600 daltons. Besides precipitating the receptor derived from cells of avirulent acapsular strain, AF II was capable of precipitating extracellular polysaccharide from cultures of virulent capsular strain, sodium polygalacturonate, and carboxymethylcellulose. These three polymers also inhibited the agglutination activity associated with AF II. AF II could be replaced by poly-l-lysines in both the precipitin and agglutination assays. In addition, in antigen absorption experiments, poly-l-lysines were found to remove the receptors for AF II from the boiled extracts of avirulent acapsular strain. Based on these observations, it is proposed that the activity of AF II resides in a highly positively charged protein which causes agglutination of bacterial cells by interacting on a charge-charge basis with negatively charged components on the surface of the bacterial cells.